CHALLENGES IN 3R IMPLEMENTATION AND PUBLIC PARTICIPATION - S.H., Fauziah; P., Agamuthu (Malaysian Journal of Science, 2013)
The increase in waste generation in the world today alarms the waste managers. The cost in managing waste keeps increasing annually while the highly preferred conventional option of waste management namely landfill disposal seems to lose its efficiency in many developing nations. Thus, implementation of an integrated waste management is crucially important to ensure that human health and environmental protection are preserved. Nevertheless, the implementation requires the adoption of various strategies since numerous factors influence the success of an integrated waste management system. Among the most vital factors is public participation. Being the main contributor of waste in a country, it is imperative that the public play an effective role in the waste management system. This research aims to discuss the challenges and 3Rs participation among the public in Malaysia. The survey targeted 625 respondents randomly selected from Klang Valley area. Series of questions were given to each respondent to determine their level of awareness in issues and challenges of 3R activities in Malaysia. Additionally, questionnaires were also formulated to determine the public attentiveness and understanding in 3Rs concepts. Collated data were analyzed to deploy the level of awareness and other relevant factors. Results indicated that the majority (83%) of respondents believed that they understand the concept of 3Rs. However, the actual responses from the assessment within the survey indicated that their main understanding is on recycling rather than 3R on the whole. These findings indicate the need for extensive campaign on 3Rs rather than on recycling strategy alone. It is necessary since Recycling is placed at the very bottom of the 3Rs practices while Reduce and Reuse are of higher priority. As for the actual practice, though more than 88% know the concept of recycling, only less than 30% practice it. Interestingly, various issues have been identified as the reasons not to participate in 3Rs activities. Among others are non-mandatory program and lack of regulations on the indiscriminate disposal of MSW. Many respondents (70%) also believe that mandatory participation in 3Rs programs would be more effective in ensuring its success. Additionally, 26% of the respondents strongly believed that the Solid Waste Management and Public Cleansing Act 2007 can be the right engine in improving the current waste management scenario in the country. In conclusion, major actions need to be instigated in order to overcome various challenges for successful implementation of 3Rs program in the country. (Keywords: 3Rs, Municipal solid waste, public participation, SPSS.)